Green Floor Tiles Energy Harvesting Using Piezoelectric Disc - Abd Manaf, Mazli Asmiza; Kok Boon Ching, (Evolution in Electrical and Electronic Engineering, 2022)
Energy harvesting using a piezoelectric material can save the energy consumption as it can be used to be one of the alternatives instead of fully using the conventional energy and the energy harvesting using the piezoelectric module is already practiced, but the energy harvesting is directly place under the floor tiles, and that kind of design has several drawbacks such as loose wiring problem, less efficient and less reliable design. The crucial objective of this research is to develop an embedded energy scavenging module using the piezoelectric concept in the floor tiles.In this research, 9 piezoelectric is used to develop the green floor tiles and the method used in this project were the piezoelectric had been embedded under the floor tiles. Then, a rectifier circuit was connected with the driver circuit in order to control the PWM signal from Arduino. The circuit was then connected to the DC-DC converter before being charged to the rechargeable battery. it can be concluded that piezoelectric discs can convert the mechanical energy from footsteps into electrical energy in AC voltage. Furthermore, the piezoelectric can be stored in an average total of 22.22 hours to charge a 12 V rechargeable battery. Thus, the green floor tiles succeed in harvesting energy using the piezoelectric and for the future work recommendation do increase the number of piezoelectric and add on a support element to the piezoelectric discs.